ANALISIS YURIDIS TERHADAP PEMBUKTIAN DALAM MENENTUKAN KERUGIAN KONSUMEN DALAM TRANSAKSI MELALUI ELEKTRONIK (Studi Pada Badan Penyelesaian Sengketa Konsumen dan Yayasan Lembaga Konsumen Indonesia di Propinsi Lampung) - Rusli Tami; Putra Adi Fahrizi (Universitas Bandar Lampung (UBL), 2022)
Breaking into security systems on the Internet is happening almost every day all over the world. The risk of transacting via the internet is very possible, intruders managed to access computers in a protected network. If there is insecurity in the computer network, it becomes a burden for business actors in terms of their responsibilities. The problem in this study is the way in which standard agreements occur through electronic means, and the power of binding agreements through electronics in Indonesian contract law, as well as evidence in determining consumer losses caused by standard agreements in electronic transactions. The research method uses a normative juridical approach and an empirical approach using secondary data, primary and tertiary data, then qualitative juridical data analysis is carried out. The results of the study, the way a standard agreement occurs via electronic means if we base it on Government Regulation Number 80 of 2019 concerning Trading Through Electronic Systems, it is the same as agreements in general, if viewed from the theory of the Consensual Principle which states that an agreement is born at the moment an agreement is reached, then the agreement it was born on the second the receipt of an offer (offerte). The power of binding agreements via electronic means in Indonesian treaty law is contained in Article 1338 paragraph (1) of the Civil Code in conjunction with Article 1320 of the Civil Code. This provision reads